Evaluasi Program Peningkatan Profesionalisme Aparatur Pemerintahan Desa Rancamulya Kabupaten Sumedang - Fadjar Trisakti; Herabudin Herabudin; Zulfa Irnawati (Publica: Jurnal Pemikiran Administrasi Negara, 2019)
This research is motivated by problems in village programs that have not been effective, the program is a village financial management training program and capacity building for the apparatus and facilitation of community empowerment. must go through several dimensions to improve the program effectiveness, efficiency, adequacy, leveling, responsiveness, the accuracy of the results of this evaluation which will later be used as input for the next village government apparatus. So that the researchers are interested in examining the Program for Professionalism Improvement of Village Government Apparatus with qualitative methods in a descriptive approach with good results. Because this can be maintained in implementing programs held by villages to improve the program to run effectively. It is better and more effective with what was done before, before the program. Because the program is indeed very important.